(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article deals with the issue of a differentiated approach to teaching the Russian language, based on artificial intelligence. It analyzes the work of prominent scientists on artificial intelligence. The problems hindering the development of Russian speech of students of military academic lyceums "Temurbeklar Maktabi" (School of Temurbeks) are studied. A model and algorithm for organizing teaching the Russian language with a differentiated approach is proposed.